Internal, external and repeated-sprint demands in small-sided games: A comparison between bouts and age groups in elite youth soccer players - Hauer, R.; Störchle, P.; Karsten, B.; Tschan, H.; Baca, A. (PLOS ONE, 2021)
This study investigated the activity profile during small-sided games (SSG) in elite youth soccer players. Internal load (IL) including heart rate (HR) and external load (EL) such as distance covered in different speed-zones (SZ) were collected from forty-eight players of three different teams (U15, U16, U18). The investigation included a total of eighteen 5vs.5 SSGs, each consisting of four 2-minute bouts on a 40x32m pitch during spring season. Total group results (n = 48) showed a reduction in total-distance (p = 0.001; = 0.12), high-intensity-running (p = 0.009; = 0.09), and low-intensity-running distance (p = 0.028; = 0.07) between bouts. Similarly, a reduction in the number of both acceleration-low (p = 0.001; = 0.12) and deceleration-high (p = 0.003; = 0.11) values was observed. Additionally, time spent in HR-zones 3 and 4 (p=0.007; = 0.10), increased, with a reduction in HR-zone 1 (p = 0.000, = 0.25). Age group comparison showed less distance covered in SZ 1 (p=0.000; = 0.56) and greater deceleration-high values (p=0.038; = 0.32) in U15 players compared to other age groups. Further, U15 showed lower values in low-intensity-running compared to U18 (p = 0.038; = 0.22). No age-related differences were found for IL and repeated sprint ability (RSA) values. The higher EL in younger age groups should be taken into account when implementing soccer specific SSGs. In addition, HRmean values between 80-85% of HRmax and RSA numbers, which are similar to match-play data, indicate SSGs as an effective training tool to prepare youth soccer athletes for the demands of competition.